The Antiaging Effect of Active Fractions and Ent-11α-Hydroxy-15-Oxo-Kaur-16-En-19-Oic Acid Isolated from Adenostemma lavenia (L.) O. Kuntze at the Cellular Level - Irmanida Batubara; Rika Indri Astuti; Muhammad Eka Prastya; Auliya Ilmiawati; Miwa Maeda; Mayu Suzuki; Akie Hamamoto; Hiroshi Takemori (Antioxidants, 2020)
Background: The extract of Adenostemma lavenia (L.) O. Kuntze leaves has anti-inflammatory activities and is used as a folk medicine to treat patients with hepatitis and pneumonia in China and Taiwan. The diterpenoid ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid (11αOH-KA) is the major ingredient in the extract and has wide-spectrum biological activities, such as antitumor and antimelanogenic activities, as well as anti-inflammatory activity. However, the physical and biological properties of this compound as an antioxidant or antiaging agent have not been reported yet. Methods: In addition to in vitro assays, we monitored antioxidative and antiaging signals in Schizosaccharomyces pombe (yeast) and mouse melanoma B16F10 cells. Results: A. lavenia water and chloroform fractions showed antioxidant properties in vitro. The A. lavenia extracts and 11αOH-KA conferred resistance to H2O2 to S. pombe and B16F10 cells and extended the yeast lifespan in a concentration-dependent manner. These materials maintained the yeast mitochondrial activity, even in a high-glucose medium, and induced an antioxidant gene program, the transcriptional factor pap1+ and its downstream ctt1+. Accordingly, 11αOH-KA activated the antioxidative transcription factor NF-E2-related factor 2, NRF2, the mammalian ortholog of pap1+, in B16F10 cells, which was accompanied by enhanced hemeoxygenase expression levels. These results suggest that 11αOH-KA and A. lavenia extracts may protect yeast and mammalian cells from oxidative stress and aging. Finally, we hope that these materials could be helpful in treating COVID-19 patients, because A. lavenia extracts and NRF2 activators have been reported to alleviate the symptoms of pneumonia in model animals.